Sigmund Freud: Perilaku Beragama - Fikria Najtama (LPPM IAIN Sorong, 2016)
This paper discusses Sigmund Freud’s view of religious behavior. The study is aimed at how the concept of religion and the consequences of psychological theories put forward against religion. Views on religion are analyzed by Islamic view. From the analysis it obtained a description that Sigmund Freud’s view it is one part only in the range of the Islamic view of human behavior. Based on his investigation of himself and his patients, he began laying the foundation of the theory of personality that is very influential on all the theories. Since then, he is determined in his life to find a purpose, namely: life is only directed to determine or guess how the arrangement of the spiritual tools and what forces affect each other and contradictory in it.